First record of the great black-backed gull (Larus marinus) in Venezuela - Casler, Clark (Boletín del Centro de Investigaciones Biológicas)
The Great Black-backed Gull (Larus marinus) was observed at the Los Olivitos estuary, Westem Venezuela, on 20 March 1990, and constitutes a new record for Venezuela. Because this species has been extending its range southward in North America, and has recently been observed on the Island of Aruba, Netherlands Antilles (1970’s), and in Colombia (1985), it may be a new arrival to Venezuela.